Cervical vascularization indices in the prediction of imminent preterm labor - Reyna-Villasmil, Eduardo (2022)
Objective: To establish the usefulness of cervical vascularization indices in theprediction of impending preterm labor. Design: Case-control study. Institution:"Dr. Urquinaona" Central Hospital, Maracaibo, Venezuela. Participants: Patientswith preterm delivery within 7 days (group A) and pregnant women with pretermdelivery beyond 7 days (group B). Methods: Pregnant women were evaluated usingtransvaginal ultrasound and followed until delivery. Main outcome measures:General characteristics, cervical vascularity indices (vascularity index, flow indexand vascularity / flow index), impending preterm delivery, and prognostic efficacy.Results: A total of 350 patients were included, 75 women presented imminentpreterm labor (group A) and 251 patients were considered as controls (group B).Patients in group A had significantly lower values of vascularization index and flowindex compared to group B (p = 0.0122 and p < 0.0001, respectively). Patients ingroup B had significantly higher values of vascularization / flow index compared topatients in group A (p = 0.0103). The three indices and the combination of these didnot show the ability to discriminate imminent preterm labor. Conclusions: Patientswith imminent preterm labor showed significant differences in the vascularizationindices compared to patients presenting preterm labor beyond 7 days of ultrasoundevaluation. However, they are not useful in predicting impending preterm labor.